PENGAWASAN PELAKSANAAN KESEPAKATAN MEDIASI PENAL DALAM PENERAPAN RESTORATIVE JUSTICE PADA TAHAPAN PENYIDIKAN - Oktobrian, Dwiki; Hendriana, Rani; Retnaningrum, Dwi Hapsari; Nurhuda, Muhammad Lukman (Faculty of Law, Universitas Pasundan, 2023)
Restorative justice in the investigation is carried out by using the penal mediation method which provides an opportunity for the Victim and the Perpetrator in a participatory way to formulate a peace agreement facilitated by the Investigator. Penal mediation comes from civil mediation with problems in the process of drafting an agreement which must be ensured that it comes purely from the Parties. This research is a socio legal research conducted at the Directorate of General Criminal Investigation of the Regional Police of Central Java and the Indonesian Advocates Association of the Semarang Branch of the Leadership Council with the methods of interviewing, observing, and reviewing case files. This research examines two problems: how the process of preparing a penal mediation agreement fits into the application of restorative justice at the investigation stage, and how to supervise the implementation of a penal mediation agreement at the investigation stage. The results of the study show that the penal mediation agreement was prepared by the Parties themselves, facilitated by the Investigator, but did not involve the community so that the orientation of returning to social harmonization was not felt. Keywords: Restorative Justice, Penal Mediation, and Investigation.